Simulation of temperature-dependent charge transport in organic semiconductors with various degrees of disorder - Heck, Alexander; Kranz, Julian; Elstner, Marcus (Journal of chemical theory and computation, 2016)
Different trends in the temperature dependence of the mobility can be observed in organic semiconductors, which constitutes a serious challenge for theoretical approaches. In this work, we apply an atomistic bottom-up simulation for the calculation of temperature-dependent mobilities of a broad selection of materials, ranging from single crystal to amorphous solid. We evaluate how well the method is able to distinguish temperature dependences of different materials and how the findings relate to experimental observations. The applied method is able to cover the full range of temperature dependencies from activated transport in amorphous materials to band-like transport in crystals. In well-characterized materials, we find good agreement with the experiment and a band-like temperature dependence. In less-ordered materials, we find discrepancies from the experiment that indicated that experimentally studied materials possess a higher degree of disorder than do the simulated defect-free morphologies.